2012
DOI: 10.1111/j.1365-313x.2011.04892.x
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin‐independent endocytosis contributes to uptake of glucose into BY‐2 protoplasts

Abstract: SUMMARYIn eukaryotic cells, several pathways exist for the internalization of plasma membrane proteins and extracellular cargo molecules. These endocytic pathways can be divided into clathrin-dependent and clathrin-independent pathways. While clathrin-dependent pathways are known to be involved in a variety of cellular processes in plants, clathrin-independent pathways have so far only been identified in animal and yeast cells. Here we show that internalization of fluorescent glucose into BY-2 cells leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…Taking into account that the major endocytic mechanism in plants depends on the coat protein clathrin 2,43 and the fact that inhibitors known to affect clathrin-dependent endocytosis provoked a remarkable delay in the rate of seed germination, the early endocytosis reported here seems to be mediated, at least in part, by chlatrin-dependent endocytosis. However, nonclathrin endocytosis has recently been reported for the internalization of glucose into BY-2 protoplasts 44 and our earlier study reported on myosin VIII-dependent fluid phase endocytosis in root cells. 11 Therefore, further studies are needed on the further analysis of the nature of plant endocytosis supporting the plant embryo germination.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that the major endocytic mechanism in plants depends on the coat protein clathrin 2,43 and the fact that inhibitors known to affect clathrin-dependent endocytosis provoked a remarkable delay in the rate of seed germination, the early endocytosis reported here seems to be mediated, at least in part, by chlatrin-dependent endocytosis. However, nonclathrin endocytosis has recently been reported for the internalization of glucose into BY-2 protoplasts 44 and our earlier study reported on myosin VIII-dependent fluid phase endocytosis in root cells. 11 Therefore, further studies are needed on the further analysis of the nature of plant endocytosis supporting the plant embryo germination.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether NGXT191 could suppress PeAPY2 in vivo, PeAPY2-transgenic lines were subjected to 0, 1.5, 3, or 6 mg mL 21 for 1.5 h followed by FM4-64 staining. The uptake of FM4-64 was calculated as the ratio of intracellular fluorescence to whole-cell fluorescence (Bandmann and Homann, 2012), and values were standardized to the wild-type control treated without NGXT191 (Kitakura et al, 2011). Wild-type and transgenic plants were examined for differences in exocytosis with BFA.…”
Section: Series 1: Apyrase Inhibitors and Bfa Treatmentmentioning
confidence: 99%
“…In plants, the mechanism and components for clathrin-dependent endocytosis have been relatively well studied (Chen et al, 2011) compared with clathrinindependent endocytosis. However, several recent studies have strongly indicated the existence of clathrin-independent pathways for endocytosis (Moscatelli et al, 2007;Onelli et al, 2008;Bandmann and Homann, 2012;Li et al, 2012). It is worth noting that the YXXФ motif does not guarantee that the protein undergoes endocytosis only by the clathrin-dependent process (Doré et al, 2001).…”
Section: Role Of the Pin-hl In Clathrin-mediated Endocytosismentioning
confidence: 99%